Subacute toxicity of phthalate and bisphenol A mixture: assessment of probiotic protective effects - Baralić, Katarina; Božić, Dragica; Živančević, Katarina; Javorac, Dragana; Antonijević Miljaković, Evica; Buha Djordjevic, Aleksandra; Ćurčić, Marijana; Bulat, Zorica; Antonijević, Biljana; Djukić-Ćosić, Danijela; Marić, Djurdjica (Archives of Pharmacy, 2022)
The aim of this study was to: (1) examine subacute toxicity of bis (2-ethylhexyl) phthalate (DEHP), dibutyl phthalate (DBP) and bisphenol A (BPA) mixture in rats and compare it with individual substance effects; (2) investigate the mechanisms of toxicity on critical target organ, testes (in vivo/in silico study); (3) examine multibiotic ability to mitigate mixture toxicity. Male rats were divided into groups (n = 6): (1) Control; (2) P (probiotic (8.78*108 CFU/kg bw/day)); (3) DEHP (50 mg/kg bw/day); (4) DBP (50 mg/kg bw/day); (5) BPA (25 mg/kg bw/day); and (6) MIX (50 mg/kg bw/day DEHP + 50 mg/kg bw/day DBP + 25 mg/kg bw/day BPA) (7) MIX + P. In silico toxicogenomic analysis was performed by Comparative Toxicogenomic Database (CTD), Citoscape software and ToppGene Suite portal. MIX led to significant changes in tissue structure (liver, kidney, spleen and testis), biochemical parameters and testosterone level of rats compared to the control group and individual substances. In silico analysis revealed 20 genes associated with DEHP/DBP/BPA and male reproductive system disorders, while the most probable mechanisms included metabolism, aryl hydrocarbon receptor pathway, apoptosis, and oxidative stress. Oxidative stress was confirmed in vivo, and changes in parameters in testicular tissue homogenates were most pronounced or present only in MIX group. Probiotic annulled/mitigated changes in biochemical, hematological, and oxidative stress parameters, relative liver mass, food consumption, and organ pathohistology. Hence, the obtained results indicate the possibility of future considerations of protective probiotic effects against phthalates and BPA mixture toxicity.